Разработка схемы пуска и работы теплофикационного блока Т-250/300-240 Харьковской ТЭЦ-5 на турбоприводе при его питании паром постороннего источника - Мамонтов, Н. И.; Гарькавенко, И. В.; Кобцев, О. М.; Воеводин, Ю. Т. (НТУ "ХПИ", 2006)
Харківським ЦКБ «Енергопрогрес» розроблено та впроваджено реконструкцію живильного турбонасоса (ПТН) турбіни Т-250/300-240 ст. №3 Харківської ТЕЦ-5. Реконструкція проточної частини власне приводної турбіни дозволила зменшити втрату тиску на регулюючому клапані та витрату пари на ПТН за збереження потрібної потужності. Також розроблено реконструкцію схеми підключення ПТН по підведенню та відведенню пари, що дозволяє здійснювати пуск енергоблоку на ПТН при живленні його парою стороннього джерела. В наслідку реконструкції ПТН підвищується економічність роботи, надійність та маневреність енергоблоку, зменшуються витрати палива під час пусків та на основних режимах.

Development and the reconstruction of nutritious turbo pump of the turbine T-250/300-240 an item №3 of Kharkov TPP-5 was developed by Kharkov central design bureau "Energoprogress". The reconstruction of a flowing part of drive turbinehas allowed to lower loss of pressure on the regulating valve and to reduce the charge steam on nutritious turbo pump at preservation of necessary output. Reconstruction of the circuit of connection nutritious turbo pump on inlet and outlet steam allowing to carry out start-up power unit on nutritious turbo pump at its feed the steam of an extraneous source also was developed. At reconstruction nutritious turbo pump the profitability of work, reliability and maneuverability power unit raises, the charge of fuel on start-up and basic modes is reduced.
Development of the circuit of start-up and work thermal clamping unit Т-250/300-240 of Kharkov TPP-5 on turbodrive at its feed the ferry of an extraneous source
Keywords: питательный электронасос; ПТН; дросселирование пара; природный газ; переходные режимы